Educational technology: assessment of a Nursing Personnel Delegation website - Juliani, Carmen Maria Casquel Monti; Kurcgant, Paulina (Revista da Escola de Enfermagem da USP, 2009)
The use of information technology is a current reality in all fields of human knowledge. Technological incorporation has taken place in healthcare services, teaching institutions, as well as in the nurse's various work processes. This study aimed at evaluating a website developed perform a Nursing Personnel Delegation Plan, a quite relevant tool in healthcare human resources management. The methodology involved quantitative research with faculty members in the field of nursing administration and students from the eight public universities in São Paulo state offering Nursing programs. Among the major results, it was pointed out that 85% of the evaluators considered the website to be excellent or satisfactory. Comments sent by e-mail were also assessed; additionally, the website's authors performed a self-evaluation. The website was considered to be useful for both the professional practice (81.7% from excellent to satisfactory) and teaching (84.6% from excellent to satisfactory).